(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The article discusses current issues in the methodology of indirect costs accounting in cotton-textile clusters. The main focus is on the problem of their rational distribution between semi-finished products (yarn, raw fabric) and finished products. The necessity of transition to improved process and multi-factor cost allocation methods is substantiated, taking into account the specific features of textile production cycles. Proposals are presented for the implementation of digital tools for accounting and standardization of distribution bases.